Identification of piecewise constant filtration parameters and boundaries of their constancy domains - Aida-zade, K. R.; Rahimov, A. B. (Automation and remote control, 2017)
Consideration was given to the numerical solution of the problem of parametric identification of the processes obeying the parabolic equations using an example of the processes of underground oil filtration. The identified parameters belong to the given functional classes such as the piecewise constant and piecewise linear functions. In the problem, needed is not only to determine the values of the coefficients, but also to identify the constancy boundaries of the coefficients. For numerical solution of the problem, an approach was suggested based on reduction of the initial problem to that of finite-dimensional optimization with a special structure of constraints. Obtained were the formulas for the gradient of the objective functional in the discretized problem allowing one to apply the efficient methods of first-order optimization. The results of numerical experiments on the model problems were presented.